Induction of Somatic Embryos and Plant Regeneration from Nodal Sprouts Culture of Adult Bamboo (Dendrocalamus strictus (Roxb.) Nees) - Kaur, Ravneet; Virk, Gurdip Singh; Nagpal, Avinash (Indian Forester, 2011)
Present investigation deals with standardization of protocol for mass Dendrocalamus strictus, through somatic embryogenesis from nodal sprout cultures. Different media supplements for the induction, development and germination of somatic embryos were studied to achieve an efficient regeneration protocol from small segments (0.5-1.0 cm) of nodal sprouts of D. strictus. For callus induction, nodal sprouts were cultured on MS medium supplemented with various concentration of 2,4-D alone or in combination with other media additives and maximum callus induction occurred on MS medium supplemented with 2,4-D at 6 mg/l. Maximum somatic embryogenesis (66.67%) was observed when callus was transferred on MS medium supplemented with a combination of 2,4-D (1 mg/l), KN (2 mg/l) and NAA (1 mg/l). The induced somatic embryos were shifted to MS medium with different concentrations of sucrose with or without activated charcoal or polyethylene glycol for somatic embryo germination. Maximum somatic embryo germination (70.83%) was noticed on MS medium enriched with 7% sucrose. The plantlets so formed were acclimatized and successfully transferred to the soil.